(untitled) (Journal of Music Research Online, 2022)
In this paper, I present a unique, interdisciplinary contribution to the continuing discourse on music’s spiritual significance by developing, after Gilles Deleuze, a theatre of the ineffable for music philosophy. The purpose of this work is to open out, rather than resolve, the existential complexity of the Romantic belief in the spirit of music, a belief which enjoys tragic, ironic, and burlesque transformation in contemporary arts theory and practice. I begin by forging and extending connections between Nietzsche, Jankélévitch and Langer where the ineffable is writ large, where the logician’s imposturous, theological aura is at stake, and where the sublime magnitude of love, faith, and mystery creates the poetic framework for rethinking anthropocentric, logocentric ontologies of music. I then introduce Deleuze’s theatre of philosophy to show its remarkable suitability for reimagining the seriousness of the ineffable, and for working with the forms of tragedy, irony and burlesque, which together render a more complex, poetic image of the music philosopher. I then look to the following works in contemporary music studies and film practice, each of which further extends the theatrical and spiritual complexity of a love and faith in the spirit of music: Steinberg’s theory of musical desire from 2014, Marcel Cobussen’s poststructural jazz studies of 2008, and Guy Maddin’s 2003 film The Saddest Music in the World. Throughout, and toward the interdisciplinary possibilities of complexity, I approach each station as an exercise in collaborative, experimental thinking, within which plural images of the music philosopher emerge.